2020
DOI: 10.1063/1.5145294
|View full text |Cite
|
Sign up to set email alerts
|

Adlayer growth vs spontaneous (near-) surface alloy formation: Zn growth on Au(111)

Abstract: As part of an extensive effort to explore the function of Au/ZnO catalysts in the synthesis of methanol from CO2 and H2, we have systematically investigated the temperature dependent growth, structure formation, and surface intermixing of Zn on the herringbone reconstructed Au(111) surface and the thermal stability of the resulting surfaces by scanning tunneling microscopy (STM) and x-ray photoelectron spectroscopy (XPS). After Zn deposition at low temperatures, at about 105 K (STM) or below (XPS), we observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 115 publications
0
5
0
Order By: Relevance
“…On the other hand, previous studies of metal atom deposition on the Au(111) surface have concluded that, compared with the growth of other metals on Au(111), Zn shows a rather high tendency for intermixing and near-surface alloy formation. 45 Note that the atomic radius of both Zn (2.01 Å) and Zn + (0.88 Å) 46 is smaller than that of Au (2.14 Å). 47 Table 1 shows calculated properties for pure Au 10 À and doped Au 9 Zn À clusters including the spin multiplicity (2S + 1), the Gibbs binding energy per particle, the average bond distances between external-external and external-central atoms (d ext-ext and d ext-cen , respectively), the HOMO-LUMO gap, and the vertical detachment energy (VDE).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, previous studies of metal atom deposition on the Au(111) surface have concluded that, compared with the growth of other metals on Au(111), Zn shows a rather high tendency for intermixing and near-surface alloy formation. 45 Note that the atomic radius of both Zn (2.01 Å) and Zn + (0.88 Å) 46 is smaller than that of Au (2.14 Å). 47 Table 1 shows calculated properties for pure Au 10 À and doped Au 9 Zn À clusters including the spin multiplicity (2S + 1), the Gibbs binding energy per particle, the average bond distances between external-external and external-central atoms (d ext-ext and d ext-cen , respectively), the HOMO-LUMO gap, and the vertical detachment energy (VDE).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, previous studies of metal atom deposition on the Au(111) surface have concluded that, compared with the growth of other metals on Au(111), Zn shows a rather high tendency for intermixing and near-surface alloy formation. 45 Note that the atomic radius of both Zn (2.01 Å) and Zn + (0.88 Å) 46 is smaller than that of Au (2.14 Å). 47…”
Section: Resultsmentioning
confidence: 99%
“…A variety of metals deposited on Au(111) have been studied, including Co, 23 Cr, 24 Fe, 25 Mn, 26 Mo, 27 Ni, 28−31 Pd, 4,32−35 Pt, 36 Rh, 37,38 Sn, 39 Ti, 40 and Zn. 41,42 Of most relevance to the present study are the STM results on the nucleation and growth of Pd islands on Au(111) by Stephenson et al 33 and Casari et al 34 Although these studies focused on the nucleation of Pd islands at room temperature (RT), they did not report on the stability of Pd islands as a function of annealing temperature as we do here. Baber et al also studied Pd on Au(111) using STM, and they discovered that the herringbone structure of Au(111) provided the entry sites for the incorporation of Pd atoms into the Au lattice and that the extent of mixing of Pd atoms with the Au surface depended on temperature.…”
Section: ■ Introductionmentioning
confidence: 82%
“…[22] Among the different single crystal surfaces of Au, the densely packed (111) orientation is the most investigated in fundamental studies of the initial stages of metal deposition. [17,18,[23][24][25] It has been reported that the deposition of lithium on Au(111) starts at underpotential shifts of more than 1 V, [23] where the first islands are deposited. [17,23] At underpotentials, subsequent layer growth covers two or more layers.…”
Section: Introductionmentioning
confidence: 99%
“…Gold single crystals are commonly used in in‐situ STM studies due to their (i) well‐defined surface structure, (ii) ease in preparation, and (iii) noble character in terms of their stability towards water and oxygen [22] . Among the different single crystal surfaces of Au, the densely packed (111) orientation is the most investigated in fundamental studies of the initial stages of metal deposition [17,18,23–25] . It has been reported that the deposition of lithium on Au(111) starts at underpotential shifts of more than 1 V, [23] where the first islands are deposited [17,23] .…”
Section: Introductionmentioning
confidence: 99%